Application of Qualitative and Quantitative Research Methods in Development Domain: Sharing of Some Anthropological Experiences from Rural Development Projects - Timseena, Bhanu (Nepalese Journal of Qualitative Research Methods, 2009)
doi: 10.3126/njqrm.v1i0.1973 Keywords: Development Domain; Rural Development Nepalese Journal of Qualitative Research Methods Vol.1 2007 pp.51-63